Multilocation Field Performance of Strip-till Drill on Wheat Crop - Shukla, L N; Dhaliwal, I S; Chauhan, A M (Journal of Agricultural Engineering, 2001)
A tractor drawn strip-till drill has been developed for successful adoption of the minimum till technology by the farmers for sowing wheat under Indian conditions. This machine has been extensively tested at research farms of P.A.U., Ludhiana and at farmers’ fields. There is no reduction in yield. The average yield for wheat at experiment stations under paddy wheat rotation for control was 3.8 t/ha while it was 3.9 t/ha for strip-till drill treatment after manually harvested paddy crop. For strip-till drill treatment in combine harvested paddy field after using stubble shaver and burning residues the average yield was 3.9 t/ha. The machine is being manufactured by local manufacturers and is readily available to the farmers.